Genetic engineering and raising temperature enhance recombinant protein production with the cdna1 promoter in Trichoderma reesei - Shanshan Jiang; Yue Wang; Qin Liu; Qinqin Zhao; Liwei Gao; Xin Song; Xuezhi Li; Yinbo Qu; Guodong Liu (Bioresources and Bioprocessing, 2022)
Abstract The fungus Trichoderma reesei is a powerful host for secreted production of proteins. The promoter of cdna1 gene, which encodes a small basic protein of unknown function and high expression, is commonly used for constitutive protein production in T. reesei. Nevertheless, the production level of proteins driven by this promoter still needs to be improved. Here, we identified that the region 600- to 700-bp upstream of the start codon is critical for the efficiency of the cdna1 promoter. Increasing the copy number of this region to three improved the production of a heterologous β-mannanase by 37.5%. Screening of several stressful conditions revealed that the cdna1 promoter is heat inducible. Cultivation at 37 °C significantly enhanced the production of β-mannanase as well as a polygalacturonase with the cdna1 promoter compared with those at 30 °C. Combing the strategies of promoter engineering, multi-copy gene insertion, and control of cultivation temperature, β-mannanase of 199.85 U/mL and relatively high purity was produced in shake flask, which was 6.6 times higher than that before optimization. Taken together, the results advance the understanding of the widely used cdna1 promoter and provide effective strategies for enhancing the production of recombinant proteins in T. reesei. Graphical Abstract